Changes of the yield condition due to accumulation of damage of metal alloys - SOCHA, G. (Engineering Transactions, 2008)
The results of the experimental investigations of fatigue damage accumulation and redis- tribution of residual stresses are reported in this paper. Local measurements of the inelastic response under constant stress amplitude were used to observe two phenomena for selected alloys. It was found that fatigue damage accumulation and redistribution of residual stress af- fect the yield condition for the investigated materials. Yield condition with damage parameter and the parameter representing residual stress state are proposed. The damage parameter is calculated, basing on the definition given in the author’s previous paper. It was also found that the yield condition and damage parameters are different for dynamic (cyclic loading) and for static (for unloaded material) conditions. Physical interpretation for the observed experimen- tal results is given in this paper. Fatigue damage accumulation is divided into three phases: cyclic stabilisation, local increase of crystal defects density, formation and propagation of the crack. Local methods of strain measurements, together with dynamic measurements of damage parameter, were found to be crucial for proper observation of fatigue damage accumulation.